Technological Modernization of Energy Companies as Basis for their Sustainable Development - Fyliuk, Halyna; Kuznetsova, Mariya (International Journal of Energy Economics and Policy, 2018)
The paper deals with the issue of sustainable development and innovative efficient performance of energy sector companies in Ukraine. In scope of the Forth Industrial Revolution and modern state of international business environment the direction of global development is inextricably linked to resource management as well as energy efficiency based on innovative approaches and technological advances. By means of extensive secondary data analysis, a comprehensive overview of current peculiarities of energy sector in Ukraine is given in order to point out major daunting tasks and define future challenges. Following the outcomes of conducted research and empirical studies, using systemic analytical approach, a broad range of the required measures to be taken are proposed. Complex strategy launch for technological modernization and innovative resource management is foreseen as a key driving force for business diversification possibilities with green practices, energy portfolio extension, establishment of full-cycle energy infrastructure and, as a result, sustainable business development. Energy management is also highlighted as a platform for mutually beneficial multi-stakeholder dialogue, the long-lasting and result-oriented one with high social inclusiveness and consciousness. Keywords: technological modernization, sustainable development, sustainability, energy efficiency, innovative resource management. JEL Classification: Q49